Changing The Subject : Mary Wroth and Figurations of Gender in Early Modern England - Miller, Naomi (Book collections on Project MUSE., 2015)
Lady Mary Wroth (c. 1587-1653) wrote the first sonnet sequence in English by a woman, one of the first plays by a woman, and the first published work of fiction by an Englishwoman. Yet, despite her status as a member of the distinguished Sidney family, Wroth met with disgrace at court for her authorship of a prose romance, which was adjudged an inappropriate endeavor for a woman and was forcibly withdrawn from publication. Only recently has recognition of Wroth's historical and literary importance been signaled by the publication of the first modern edition of her romance, The Countess of Mou.